Relocation of Aurora B from centromeres to the central spindle at the metaphase to anaphase transition requires MKlp2. - Gruneberg, U; Neef, R; Honda, R; Nigg, E; Barr, F (2004)
Mitotic kinases of the Polo and Aurora families are key regulators of chromosome segregation and cytokinesis. Here, we have investigated the role of MKlp1 and MKlp2, two vertebrate mitotic kinesins essential for cytokinesis, in the spatial regulation of the Aurora B kinase. Previously, we have demonstrated that MKlp2 recruits Polo-like kinase 1 (Plk1) to the central spindle in anaphase. We now find that in MKlp2 but not MKlp1-depleted cells the Aurora B-INCENP complex remains at the centromeres and fails to relocate to the central spindle. MKlp2 exerts dual control over Aurora B localization, because it is a binding partner for Aurora B, and furthermore for the phosphatase Cdc14A. Cdc14A can dephosphorylate INCENP and may contribute to its relocation to the central spindle in anaphase. We propose that MKlp2 is involved in the localization of Plk1, Aurora B, and Cdc14A to the central spindle during anaphase, and that the integration of signaling by these proteins is necessary for proper cytokinesis.